2005
DOI: 10.1177/0272989x05276852
|View full text |Cite
|
Sign up to set email alerts
|

Is Antibiotic Prophylaxis for Bacterial Endocarditis Cost-Effective?

Abstract: Predental antibiotic prophylaxis is cost-effective only for persons with moderate or high risk of developing endocarditis. Contrary to current recommendations, our data demonstrate that amoxicillin and ampicillin are not cost-effective and should not be considered the agents of choice. Clarithromycin should be considered the drug of choice and cephalexin as an alternative drug of choice. The current published guidelines and recommendations should be revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 41 publications
1
39
0
2
Order By: Relevance
“…Clearly, this is a much higher fatal ADR rate than previously estimated and similar to our rates for all other uses of clindamycin (11/million). While the non-fatal ADR rate was considerably less than previously estimated (4000/million), 14 it was again similar to our rates for all other uses of clindamycin (270/million). These data suggest that use of clindamycin for AP carries a significant risk of ADRs that is very similar to the risk associated with the use of clindamycin for treating infections.…”
Section: Adverse Reactions To Clindamycinsupporting
confidence: 89%
“…Clearly, this is a much higher fatal ADR rate than previously estimated and similar to our rates for all other uses of clindamycin (11/million). While the non-fatal ADR rate was considerably less than previously estimated (4000/million), 14 it was again similar to our rates for all other uses of clindamycin (270/million). These data suggest that use of clindamycin for AP carries a significant risk of ADRs that is very similar to the risk associated with the use of clindamycin for treating infections.…”
Section: Adverse Reactions To Clindamycinsupporting
confidence: 89%
“…A total of five relevant stud ies were identified that considered both costs and outcomes. [16][17][18][19][20] These studies provided contradictory evidence on the cost-effectiveness of antibiotic prophy laxis for at-risk patients undergoing interventional procedures. However, it has been commonly observed that peni cillin could result in many more deaths (at least in the short term) secondary to anaphylaxis compared with a strategy of no prophylaxis.…”
Section: Published Health Economics Literaturementioning
confidence: 99%
“…Evidence on the cost effectiveness of antibiotic prophylaxis for at-risk patients undergoing interventional procedures is contradictory as well. [12][13][14][15][16] Without any clear evidence of benefit, the traditional empiric approach for antibiotic prophylaxis has been in vogue, thus far, primarily thanks to the apprehension about the serious nature of infective endocarditis among physicians, as well as among patients, reinforced by past recommendations from professional societies. Emergence of antibiotic resistance as a significant public health concern combined with the risk of antibiotic-related adverse effects, albeit infrequent, such as anaphylaxis or Clostridium difficile colitis, has prompted a steady move towards an evidence-based approach to infective endocarditis prophylaxis.…”
Section: Evidence-based Approach To Infective Endocarditismentioning
confidence: 99%